Current account dynamics in a small open economy model of status seeking - Walter H. Fisher (Institute for Advanced Studies (IHS), 2001)
In this paper we will use a status-preference framework, together with a standard cost of adjustment investment function, to study the dynamics of the small open economy current account balance. We demonstrate that the transitional dynamics of the economy is characterized by two speeds of adjustment: a speed of adjustment arising from statuspreference and a speed of adjustment arising from installation costs of investment. This structure implies that the current account balance depends on both speeds of adjustment as well as on the long-run equilibrium. As a consequence, the current account can exhibit nonmonotonic behavior in transition to the steady state.
Keywords: E21; F41; 330; current account; status seeking; relative wealth; open economy dynamics; Leistungsbilanz; Kleines-offenes-Land; Monetäre Außenwirtschaftstheorie; Theorie